Sanksi Hukum Terhadap Rumah Sakit yang Melakukan Pencemaran Lingkungan dengan Sampah Alat-Alat Kesehatan - Cahya Edy Priana; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2024)
Hospitals are a double burden on society because despite offering much-needed medical care, they also risk spreading disease and contributing to pollution due to the waste they produce. The formulation of the problem from this study is: How is the legal regulation for hospitals that pollute the environment with medical equipment waste? and What are the legal sanctions against hospitals that pollute the environment with medical equipment waste? This type of research uses normative legal research with the type of approach used is a statutory approach. Legal material is collected through literature studies and the analysis method that researchers will use is qualitative descriptive. The results of the analysis of the regulation of the Hospital Law that pollutes the environment with medical equipment waste are contained in the Law of the Republic of Indonesia Number 32 of 2009 concerning Environmental Protection and Management. Legal sanctions against hospitals that pollute the environment with plastic medical device waste where hospitals that dispose of medical waste carelessly will be subject to legal sanctions in the form of revocation of the hospital's operating license and punished with a maximum imprisonment of 3 (three) years and a maximum fine of Rp. 3,000,000,000,000,00 (three billion rupiah)